2012
DOI: 10.1155/2012/914035
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Posterior Reversible Encephalopathy Syndrome Potentially Related to AIDS and End-Stage Renal Disease: A Case Report and Review of the Literature

Abstract: Posterior reversible encephalopathy syndrome (PRES) is a clinicoradiological syndrome that is characterized by clinical features including headache, altered mental status, cortical blindness, seizures, and other focal neurological signs as well as subcortical edema without infarction on neuroimaging. Under the umbrella of hypertensive encephalopathy, PRES is defined by reversible cerebral edema due to dysfunction of the cerebrovascular blood-brain barrier unit. The pathophysiology of PRES is thought to result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…While the patterns of distribution of such signal hyper intensities are now known to vary, historically PRES was thought to produce bilateral and symmetric lesions in the posterior temporal, parietal, and occipital regions of the brain [2,6]. The posterior circulation was believed to be preferentially affected due to its relatively poorer sympathetic innervation [13]. Cohort studies [6,12] have described four different radiological patterns of PRES and reported that this archetypal pattern, referred to as ‘the dominant parietal-occipital pattern’, occurred in only 22% in their studied cohort of 136 cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While the patterns of distribution of such signal hyper intensities are now known to vary, historically PRES was thought to produce bilateral and symmetric lesions in the posterior temporal, parietal, and occipital regions of the brain [2,6]. The posterior circulation was believed to be preferentially affected due to its relatively poorer sympathetic innervation [13]. Cohort studies [6,12] have described four different radiological patterns of PRES and reported that this archetypal pattern, referred to as ‘the dominant parietal-occipital pattern’, occurred in only 22% in their studied cohort of 136 cases.…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection has been implicated as the etiological factor in many published cases of PRES [8,9,11,13]. HIV virus has been shown to induce endothelial cell apoptosis, tight junction disruption, oxidative stress, and the expression of pro-inflammatory cytokines and adhesion molecules which stimulate endothelial cell inflammation, all of which culminates in BBB dysfunction [11,16,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, antiretroviral therapy has been observed to cause PRES [3,4,5]. Alternatively, HIV patients receiving non-HIV-related treatment that results in additional immunosuppression, have also been reported [6,7,8,9]. PRES due to the actual immunosuppression of HIV, without the administration of HIV therapy is much less well-documented [1, 10, and 11].…”
Section: Discussionmentioning
confidence: 99%